Biochar for the Control of Plant Pathogens - Ramesh, Sneha; Babu, Subramanian (Journal of Scientific Agriculture, 2023)
Biochar, the solid product of pyrolysis of biomass at thermal degradation temperatures, is useful in agriculture as manure for enhancing plant growth through the supply of nutrients. It is used in protected cultivation practices of vegetables and flower crops in the pot culture and grow bags especially to improve soil physicochemical properties, and in hydroponics to remove pollutants like heavy metals in the water. The usage of biochar as a potential soil amendment for plant growth promotion, improving soil fertility and plant disease suppression are being explored in recent years. Biochar made from many of the agro waste materials was found to suppress the plant pathogens in the soil and also effective in controlling the pathogens affecting aerial parts of the plants. Although direct antifungal or antibacterial effects and metabolites of biochar are poorly understood, induced systemic resistance in plants through signal transduction and expression of defence chemicals and metabolites have been studied. In addition, microbiome analyses through metagenome sequencing revealed an increase in the population of beneficial microbes (antagonistic to plant pathogens) in the rhizosphere soils applied with biochar.